Pentingnya Penerapan Keselamatan Dan Kesehatan Kerja (K3) Sebagai Faktor Penentu Optimalisasi Produktivitas Kerja - Robi Rojaya Simbolon; Farrel Pasya Harramain; Mochamad Rizaldi Putra Sonjaya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Occupational health and safety (K3) is an effort to protect things that are dangerous so that everyone in the work environment is always safe and healthy. Creating a safe and healthy work environment can minimize the occurrence of accidents or accidents that can cause prolonged absences from work and significant costs for the company. Injured or sick workers can hinder productivity and disrupt work. The implementation of work safety basically aims to find weaknesses that exist and the possibility of accidents occurring in the work environment. This function consists of finding the cause and effect of an accident and investigating whether it is controllable or not. Labor productivity is a very important factor for companies, because the higher labor productivity, the more production or work results that can be provided in a certain time. To achieve maximum productivity, other things that are still related to labor productivity must also be considered. Among them are job opportunities, work motivation, work efficiency and effectiveness, work ability, as well as experience and knowledge that support the work process. Measurement of labor productivity is based on a system of physical income per person or hours worked per person based on working time or in days or years. By making these measurements, it is converted into work units, namely. into the amount of work that can be completed by employees working according to implementation standards in one hour. In short: The adoption of occupational health and safety in the workplace is an important factor in increasing the productivity and success of the entire enterprise. With the implementation of OSH it is possible to prevent work-related accidents and injuries, prevent employee absenteeism, which increases job satisfaction and creates competitive advantages that can lead to future employee success.